Effects of field position on fluid balance and electrolyte losses in collegiate women`s soccer players - Wang, H.; Early, K. S.; Theall, B. M.; Lowe, A. C.; Lemoine, N. P.; Marucci, J.; Mullenix, S.; Johannsen, N. M. (Medicina, 2020)
Research investigating hydration strategies specialized for women`s soccer players is limited, despite the growth in the sport. The purpose of this study was to determine the effects of fluid balance and electrolyte losses in collegiate women`s soccer players. Eighteen NCAA Division I women`s soccer players were recruited (age: 19.2 ± 1.0 yr; weight: 68.5 ± 9.0 kg, and height: 168.4 ± 6.7 cm; mean ± SD), including: 3 forwards (FW), 7 mid-fielders (MD), 5 defenders (DF), and 3 goalkeepers (GK). Players practiced outdoor during spring off-season training camp for a total 14 practices (WBGT: 18.3 ± 3.1 °C). The main outcome measures included body mass change (BMC), sweat rate, urine and sweat electrolyte concentrations, and fluid intake. Results were analyzed for comparison between low (LOW; 16.2 ± 2.6° C, n = 7) and moderate risk environments for hyperthermia (MOD; 20.5 ± 1.5 °C, n = 7) as well as by field position. The majority (54%) of players were in a hypohydrated state prior to practice. Overall, 26.7% of players had a %BMC greater than 0%, 71.4% of players had a %BMC less than -2%, and 1.9% of players had a %BMC greater than -2% (all MD position). Mean %BMC and sweat rate in all environmental conditions were -0.4 ± 0.4 kg (-0.5 ± 0.6% body mass) and 1.03 ± 0.21 mg·cm-2·min-1, respectively. In the MOD environment, players exhibited a greater sweat rate (1.07 ± 0.22 mg·cm-2·min-1) compared to LOW (0.99 ± 0.22 mg·cm-2·min-1; p = 0.02). By position, DF had a greater total fluid intake and a lower %BMC compared to FW, MD, and GK (all p < 0.001). FW had a greater sweat sodium (Na+) (51.4 ± 9.8 mmol·L-1), whereas GK had the lowest sweat sodium (Na+) (30.9 ± 3.9 mmol·L-1). Hydration strategies should target pre-practice to ensure players are adequately hydrated. Environments deemed to be of moderate risk of hyperthermia significantly elevated the sweat rate but did not influence fluid intake and hydration status compared to low-risk environments. Given the differences in fluid balance and sweat responses, recommendations should be issued relative to soccer position.